2011
DOI: 10.1242/jcs.078261
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase Rpd3 regulates the heterochromatin structure ofDrosophilatelomeres

Abstract: SummaryTelomeres are specialized structures at the end of eukaryotic chromosomes that are required to preserve genome integrity, chromosome stability and nuclear architecture. Telomere maintenance and function are established epigenetically in several eukaryotes. However, the exact chromatin enzymatic modifications regulating telomere homeostasis are poorly understood. In Drosophila melanogaster, telomere length and stability are maintained through the retrotransposition of specialized telomeric sequences and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Furthermore, we have shown that the telomeres in mutants with looping defects are more susceptible to uncapping, nucleolytic degradation, telomere loss and promote accelerated rates of cellular senescence in the absence of telomere maintenance. A recent study has reported that the Rpd3 complex is required to prevent chromosome end fusions in Drosophila melanogaster [37]. Together, these data suggest that the regulation of such telomere fold-back structures may be conserved, and furthermore indicate that multiple cellular processes, apart from those that directly impinge on DNA metabolism, may have effects on telomere structure/function.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, we have shown that the telomeres in mutants with looping defects are more susceptible to uncapping, nucleolytic degradation, telomere loss and promote accelerated rates of cellular senescence in the absence of telomere maintenance. A recent study has reported that the Rpd3 complex is required to prevent chromosome end fusions in Drosophila melanogaster [37]. Together, these data suggest that the regulation of such telomere fold-back structures may be conserved, and furthermore indicate that multiple cellular processes, apart from those that directly impinge on DNA metabolism, may have effects on telomere structure/function.…”
Section: Discussionmentioning
confidence: 81%
“…Similar results were reported for rpd3 mutants at telomeres; specifically, this is true for H4K12 in yeast (Ehrentraut et al ., 2010) and for several H4 lysine residues in Drosophila (Burgio et al ., 2011). Our observation represents the first evidence of hypoacetylation at rDNA of rpd3 mutants.…”
Section: Resultsmentioning
confidence: 99%
“…At this locus Rpd3p is necessary for heterochromatin boundary formation, inhibiting the SIR complex spreading along subtelomeric genes (Zhou et al ., 2009; Ehrentraut et al ., 2010). Moreover , rpd3 mutants show H4 hypoacetylation, particularly at Lys-16, also in the Drosophila telomeres (Burgio et al ., 2011). It was hypothesized that Rpd3p interacts with chromatin at boundary regions, where its activity on H4K12 and H4K5 would create a chromatin environment able to block Sir2p-dependent H4K16 deacetylation (Zhou et al ., 2009; Ehrentraut et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Then polytene chromosomes were processed as described previously 24 , using the same primary antibody of Western blot analysis (Upstate, Greenville, SC, # 06-599). DNA was stained with DAPI.…”
Section: Analysis Of Polytene Chromosomesmentioning
confidence: 99%